2002
DOI: 10.1038/sj.jhh.1001426
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of insulin resistance and postprandial triglyceride response in newly diagnosed hypertensive patients with hypertriglyceridaemia

Abstract: The purpose of the study is to examine the differences in insulin resistance and postprandial triglyceride (TG) response between hypertensive patients with or without hypertriglyceridaemia. The study is a comparative cohort study with matching. Thirty-one newly diagnosed hypertensive patients without any medication were recruited from a health survey. The participants were further divided into two groups: those with fasting TG Ͻ2.26 mmol/L, and those with TG between 2.26 and 5.65 mmol/L. Both groups were match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Thus, Kolovou et al [8] have concluded that fasting TAG status is a significant indicator of an exaggerated rise in postprandial TAG. Along with significantly higher fasting TAG in our HTAG group, we observed an augmented postprandial TAG response in these same subjects despite no differences in waist circumference, BMI or percentage body fat, a finding that is consistent within the mixed-meal literature [8,9,47,48]. This is of particular interest as visceral adipose tissue has been suggested to be a significant contributor to the degradation of postprandial TAG [50].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, Kolovou et al [8] have concluded that fasting TAG status is a significant indicator of an exaggerated rise in postprandial TAG. Along with significantly higher fasting TAG in our HTAG group, we observed an augmented postprandial TAG response in these same subjects despite no differences in waist circumference, BMI or percentage body fat, a finding that is consistent within the mixed-meal literature [8,9,47,48]. This is of particular interest as visceral adipose tissue has been suggested to be a significant contributor to the degradation of postprandial TAG [50].…”
Section: Discussionsupporting
confidence: 89%
“…Postprandial TAG dysfunction associated with hypertriglyceridemia has been observed in studies of healthy men with low or high fasting TAG status [9,47], in subjects with metabolic syndrome [8], postmenopausal women [48] and in subjects with type 2 diabetes [49]. Thus, Kolovou et al [8] have concluded that fasting TAG status is a significant indicator of an exaggerated rise in postprandial TAG.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the functional effect of the LPL haplotypes, we performed a trial on 20 homozygote subjects that either carried risk haplotypes or protective haplotypes of LPL. These subjects consumed a meal with high fat (66% of calories from lipids) [Hwu et al, 2002]. The postheparin serum from these subjects was then used to detect LPL expression by western blot analysis.…”
Section: High Fat Loading Trial For Lpl Expression Measurementmentioning
confidence: 99%
“…To obtain plasma excursions of glucose, insulin, C-peptide, TG, and FFA, 100-l blood samples were collected at 10,15,20,30,45,60,120,180, and 240 min after the load (total blood sample volume Ͻ5% of total blood volume). After collection of the final sample, rats were given a lethal dose of Na-thiobutabarbitol.…”
Section: Acute Studymentioning
confidence: 99%
“…Even in healthy individuals, consumption of a meal containing fat produces postprandial TG excursions that persist for many hours and can impair the ability of insulin to regulate glucose metabolism in the postprandial phase of the subsequent meal (13,41). Exacerbated postprandial hypertriglyceridemia, associated with insulin resistance, is evident in patients with newly diagnosed hypertension (20) and patients with type 2 diabetes (33), including their first-degree relatives (3). This manifestation of the metabolic syndrome may be especially important in light of evidence linking exaggerated postprandial hyperlipidemia and coronary artery disease (22,40).…”
mentioning
confidence: 99%